Artefatos ou instrumentos no Métier do professor de língua inglesa da rede pública: recursos tecnológicos e o agir docente nos textos de instrução ao sósia - Riciolli, Ana Maria Barbosa Varanda [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work analyzed the acting of two English (LI) teachers (named S1 and S2) of municipal public Elementary schools from Joviânia (GO State). Whereby the Instruction to the Double - ID procedure (CLOT, 2007a), texts of S1 and S2 where produced in a context of use of technology, aiming at investigating which is the representation revealed in the language actions of those teachers and how they transfer that image to their pedagogical practice in English teaching. It was used computational tool AntConc to organize the analysis of the collected data. Therein, the aim of this work was to infer the dimensions of instrumental genesis from the linguistic-discursive elements found in the texts, such as instrumentation and instrumentalization, from the point of view of Socio-Discursive Interactionism (BRONCKART, 2009) and instrumental approach (RABARDEL, 1995, 2002; RABARDEL & WAERN, 2003). This approach focuses on Vygotsky's ideas, emphasizing that an instrument consists of an intermediate element which stands between psychic operations and the device. Acting over it, it is the instrument that will determine human activity. Even if a material or symbolic resource is available to a user for a given task, it will only be useful if the user knows which tasks correspond to the proposed activity and how they do it (RABARDEL, 2002). When it comes to language and the educational duty, Clot (2007a) emphasizes that the subject expresses in words their thoughts about work and in work situation. These texts are relevant for the comprehension of the teacher's action, therefore, once collected, data were selected and classified according to the theoretical and methodological frame of ALTER group, which is anchored to the Socio-Discursive Interactionism - ISD (BRONCKART, 2006, 2007, 2008, 2009; BRONKCART, MACHADO, 2004; MACHADO et al., 2009a, 2009b). From the speeches produced by the ID, it is possible to see that S1 and S2 both report, whereby their ...

Este trabalho analisou o agir de duas professoras de Língua Inglesa (LI) (nomeadas de S1 e S2), da rede pública municipal de Educação Básica da cidade de Joviânia (GO). Por meio do procedimento de Instrução ao sósia - IS (CLOT, 2007a), foram produzidos os textos de S1 e S2 em situação de uso da tecnologia, visando investigar qual é a representação manifestada no agir linguageiro das professoras e como transferem essa imagem para sua prática pedagógica no ensino de língua inglesa. Foi utilizada a ferramenta computacional AntConc para organizar a análise dos dados coletados. Nesse sentido, o objetivo deste estudo foi depreender, através dos elementos linguístico-discursivos encontrados nos textos, as dimensões da gênese instrumental, quais sejam, instrumentação e instrumentalização, à luz do interacionismo sociodiscursivo (BRONCKART, 2009) e da abordagem instrumental (RABARDEL, 1995, 2002; RABARDEL & WAERN, 2003). Esta abordagem enfoca as ideias de Vygotsky, destacando que um instrumento compõe um elemento intermediário que se estabelece entre as operações psíquicas e o artefato. Operando sobre ele, é o instrumento que vai determinar a atividade humana. Mesmo que um recurso, material ou simbólico, esteja à disposição de um usuário para uma determinada tarefa, só terá utilidade se esse usuário souber quais tarefas se encaixam na atividade proposta e de que maneira o fazem (RABARDEL, 2002). No que se refere à linguagem e à tarefa educacional, Clot (2007a) destaca que o sujeito coloca em palavras suas reflexões sobre o trabalho e em situação de trabalho. Esses textos são relevantes para a compreensão do agir do professor, por isso, após a coleta dos dados, foram selecionados e classificados dentro do quadro teórico-metodológico do grupo ALTER, que está ancorado no interacionismo sociodiscursivo - ISD (BRONCKART, 2006, 2007, 2008, 2009; BRONKCART, MACHADO, 2004; MACHADO et al., 2009a, 2009b)...
Keywords: Língua inglesa; Professores; Linguística; English language